Do invasive species perform better in their new ranges?. Issue 5 (1st May 2013) - Parker, John D.; Torchin, Mark E.; Hufbauer, Ruth A.; Lemoine, Nathan P.; Alba, Christina; Blumenthal, Dana M.; Bossdorf, Oliver; Byers, James E.; Dunn, Alison M.; Heckman, Robert W.; Hejda, Martin; Jarošík, Vojtěch; et al.
Abstract : A fundamental assumption in invasion biology is that most invasive species exhibit enhanced performance in their introduced range relative to their home ranges. This idea has given rise to numerous hypotheses explaining "invasion success" by virtue of altered ecological and evolutionary pressures. There are surprisingly few data, however, testing the underlying assumption that the performance of introduced populations, including organism size, reproductive output, and abundance, is enhanced in their introduced compared to their native range. Here, we combined data from published studies to test this hypothesis for 26 plant and 27 animal species that are considered to be invasive. On average, individuals of these 53 species were indeed larger, more fecund, and more abundant in their introduced ranges. The overall mean, however, belied significant variability among species, as roughly half of the investigated species ( N = 27) performed similarly when compared to conspecific populations in their native range. Thus, although some invasive species are performing better in their new ranges, the pattern is not universal, and just as many are performing largely the same across ranges.